The contribution of information communication technology (ICT) to total factor productivity (TFP) and economic growth: Evidence from Asia-Pacific and EU countries / Farzaneh Khalili - Khalili, Farzaneh (2014)

(untitled)
The impact of information and communications technology (ICT) on the economy has become a fundamental part of industrial economics. This is due to the key role played by ICT in the industrial sector and economy as a whole. When ICT is considered as just an input under the growth accounting approach, it fails to capture the impact of ICT as a Solow residual. This thesis, through the use of two channels, firstly, the growth accounting approach, and, secondly, the endogenous growth model, fully captures the spillover effects of ICT on economic growth. To overcome the methodological limitation found in previous studies, this thesis has adopted a relatively new panel data techniques and added new controlling variables that are expected to have potential as additional growth drivers. We have used two different panel data approaches to estimate the ICT effects. Firstly, Pooled Mean Group (PMG), Mean Group (MG) and Dynamic Fixed Effect (DFE) estimators are applied to identify the direction of causality under vector error correction representation. Secondly, to deal with the endogeneity problem, Generalised Methods of Moments (GMM) estimators are employed to estimate the long run association among labour employment, ICT, non-ICT, TFP contribution and output growth through cross-industry and cross-country analyses. The sample period covers from 1990 to 2011 of which is further divided into two sub-periods, 1990 to 2000 and 2001 to 2011 respectively. This study obtains empirical results from a group of countries at the aggregate and industrial levels. The industrial level findings reveal that there is a unidirectional short run causal relationship running from economic growth to ICT contribution for Japan, Finland and Denmark but that relationship is bidirectional in the long run. Furthermore, the dynamic panel results for Sweden and Australia show bidirectional causality among ICT, TFP contribution and economic growth both in the long run and short run. ICT has no significant effect on TFP growth in Japan and Finland, whereas a negative relationship between ICT and TFP may reveal a IV productivity paradox in Denmark, Australia and Sweden. The outcomes in five countries show that returns were smaller in ICT-using than ICT-producing industries and that no significant complementary impacts exist between ICT and non-ICT capital. At the country level, GMM estimates indicate that the long run growth impact of ICT in the Asia-Pacific and EU countries is not uniform between two sub-periods. The growth impact of ICT was stronger in Asia-Pacific countries during the first sub-period as opposed to the EU. In contrast, EU led Asia-Pacific countries in the second sub-period. For short run causality, it is found that there is unidirectional flow from GDP growth to ICT contribution for both regions. Moreover, the EU countries benefit from the spillover effects of ICT whereas there is no causal relationship between ICT and TFP growth in Asia-Pacific countries. Aggregating at the country level, the result reveals that ICT has a higher positive spillover effect on value added growth through TFP in ICT developed countries as compared to ICT less developed countries. The thesis concludes with a few policy implications. First, the effect of ICT on growth is not static but a long and dynamic process. Second, there is robust potential to exploit growth profits in service industries that make intensive use of ICT. Finally, advocating ICT diffusion within the economy is much more growth enhancing than just concentrating on the ICT-producing sectors.